Prolonged Use of Protective Masks Induced Facial Skin Injury in Primary Healthcare Workers during COVID-19 Pandemic: A Systematic Review - Yapanto, Alvian Mohamad; Isnaeni, Aulia Rahma; Lestari, Khairani Ayu; Satyarsa, Agung Bagus Sista (Indonesian Journal of Tropical and Infectious Disease, 2022)
COVID-19 transmission necessitates health workers to use personal protective equipment (PPE), especially protective masks when delivering medical services. Long-term use of protective masks might cause facial skin injuries. Our study aims to provide a systematic review to explore the phenomenon and incidence of protective masks induced facial skin injuries in primary healthcare workers. This systematic review was created by obtaining articles from the PubMed database and the Cochrane library from 2020 to 2021, using the keywords "Face skin injury," "Wearing protective masks for a long time," and "Wearing protective masks and facial skin disorders." Inclusion criteria were studies that fully report the phenomenon of wearing protective masks and the incidence of facial skin injuries. One hundred and sixty-eight studies were obtained, but only 14 articles matched the inclusion criteria with more than 10,430 participants from different countries that covered various characteristics of facial skin injuries in primary healthcare workers. The findings obtained dominant characteristics of health workers who experienced facial skin injuries: women, N95 masks, and daily N95 coverage for more than 6 hours (p<0.05). Facial skin injuries are often seen after using protective face masks, as it is used for an extended period as part of a defensive effort during work. Therefore, measures that protect health workers from COVID-19 and prevent health workers from potential injuries of protective masks must be taken into account.